2000
DOI: 10.1093/jac/46.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a hepadnavirus by electrolysed acid water

Abstract: Glutaraldehyde is used as a disinfectant for endoscopes, but is an irritant and so should be replaced by an alternative. Electrolysed acid water (EAW) has a bactericidal effect, and an endoscopic washing device using EAW has been developed in Japan. To investigate the effect of EAW on the infectivity of viruses, we treated duck hepatitis B virus (DHBV), which has similar properties to hepatitis B virus, with EAW, and determined the number of remaining infectious virus particles in a bioassay system. One-day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…An immunoassay has been used to assess ECAS a -treated hepatitis B virus (HBV) surface antigen (in the absence of an appropriate whole-cell bioassay) and a significant concentrationdependent reduction in the measured antigenicity was observed [93]. The authors postulated that this was indicative of a reduction in the infectivity of human HBV [93] and this is supported by the finding that ECAS a reduced the infectivity of a hepatitis B surrogate, duck hepatitis B virus, indicating the efficacy of ECAS a against hepadnaviruses [92]. Similarly, the ECAS a treatment of the norovirus surrogate bacteriophage MS2 was shown to significantly reduce infectivity, although significantly longer exposure times were required for surface-associated virions, presumably due to reduced accessibility of the active moieties [94].…”
Section: Virusesmentioning
confidence: 98%
See 2 more Smart Citations
“…An immunoassay has been used to assess ECAS a -treated hepatitis B virus (HBV) surface antigen (in the absence of an appropriate whole-cell bioassay) and a significant concentrationdependent reduction in the measured antigenicity was observed [93]. The authors postulated that this was indicative of a reduction in the infectivity of human HBV [93] and this is supported by the finding that ECAS a reduced the infectivity of a hepatitis B surrogate, duck hepatitis B virus, indicating the efficacy of ECAS a against hepadnaviruses [92]. Similarly, the ECAS a treatment of the norovirus surrogate bacteriophage MS2 was shown to significantly reduce infectivity, although significantly longer exposure times were required for surface-associated virions, presumably due to reduced accessibility of the active moieties [94].…”
Section: Virusesmentioning
confidence: 98%
“…Numerous studies have demonstrated the virucidal activity of ECAS a against a broad range of targets [48, 51, 61, [92][93][94][95][96][97], comparable to that of other biocidal agents [92]. Most methodologies expose virus particles in suspension to ECAS a in the presence/absence of organic loading, whereby ECAS a reduces the number of viable virus particles as measured by cytopathic effects of the target virions in subsequently infected cell lines [48,51].…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrolyzed strongly acidic water (ESW) has been widely used for infection control in clinical settings (7,9) because it has been proved to be effective for the disinfection of disinfectant-resistant bacteria, such as Mycobacteria (15), Pseudomonas aeruginosa (6), and spore-forming bacteria (3,4,6), and viruses causing blood-borne infections such as hepatitis B virus (8,11) and HIV (5). ESW is also expected to be used against pathogens of emerging diseases, such as the avian influenza virus H5N1 (12).…”
Section: -10mentioning
confidence: 99%
“…High-level disinfectants, such as glutaraldehyde (GA), have disinfection potentials against any microorganisms; however, it has been reported that it may be harmful to patients and healthcare workers (1,2). ESW is considered less toxic than GA (13), and it has been reported to be effective against disinfectantresistant bacteria, such as Pseudomonas aeruginosa (6), spore-forming bacteria (3,4,6), and bloodborne infectious pathogens such as hepatitis B virus (8,11) and HIV (5) depending on the condition. Further study is needed to clarify both the disinfection spectrum of ESW and the optimum conditions for disinfection, particularly the relationship between smaller apparatus with the positive electrode and then re-electrolyzed at a constant voltage of 24 V for 7 min.…”
Section: -10mentioning
confidence: 99%